(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
This article constitutes a possible critical-reflexive reading of the show directed by Ione de Medeiros, from Grupo Oficcina Multimédia (GOM), premiered in 2023, for the play Vestido de noiva, written by Nelson Rodrigues in 1943. To this end, the text is composed of two parts: the first consists of an investigation into Nelson Rodrigues’ important contributions to modern Brazilian theater; and the second reveals some elements of GOM’s multimedia language that structure the recent theatrical production, Vestido de noiva, in order to expand and revive rodriguiano’s theatrical text.